AN ANALYSIS OF STUDENTS DIFFICULTIES IN PRONOUNCING ENGLISH VOWEL - Raodatul Jannah; Jismulatif Jismulatif; Maria Safriyanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is a descriptive-quantitative research design which is aimed at investigating the difficulties of second semester students’ English Education Study Program at Teacher Training and Education Faculty of Universitas Riau in pronouncing English vowel. The subjects of this study were the second semester students’ English Education Study Program at Teacher Training and Education Faculty of Universitas Riau. 32 students employed in this study were given the Pronounciation Test. The findings of this study revealed that the student knew about their difficulties in pronouncing English vowel. This result showed that the participants had good pronounciation skill. Based on this research the mean score of second semester students of English Education Study Program at Teacher Training and Education Faculty of Universitas Riau were good.Key Words: Pronounciation, English Vowel, English Education Sudy Program.